2014
DOI: 10.1016/j.acap.2014.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Sickle Cell Disease Cases Using Administrative Claims

Abstract: This definition can be used to facilitate a more accurate identification of children with SCD in future studies. Further investigation is necessary to determine whether this method translates to other populations besides Michigan Medicaid-insured children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 28 publications
1
101
0
Order By: Relevance
“…Second, we used a single claim to define CP and osteoporosis. Previous validation studies have shown that two or more claims for a medical condition tend to improve accurate identification of that medical condition . However, accurately identifying medical conditions depends on the number of years for the study period and the medical condition examined .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, we used a single claim to define CP and osteoporosis. Previous validation studies have shown that two or more claims for a medical condition tend to improve accurate identification of that medical condition . However, accurately identifying medical conditions depends on the number of years for the study period and the medical condition examined .…”
Section: Discussionmentioning
confidence: 99%
“…Previous validation studies have shown that two or more claims for a medical condition tend to improve accurate identification of that medical condition . However, accurately identifying medical conditions depends on the number of years for the study period and the medical condition examined . A single claim‐based definition for identifying a pediatric‐onset disability and osteoporosis performs better compared with other medical conditions, with positive predictive values of approximately 80% and up to 92%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific types of health services were considered, as these services can have different predictive values for identifying cases in other chronic conditions . Counts of claims or service types ranged from at least one to at least 3; previous findings indicate that little specificity would be gained by requiring additional claims and would result in loss of sensitivity . Definitions with varying lengths between outpatient visits were also considered, consistent with other administrative claims‐based definitions for chronic conditions .…”
Section: Methodsmentioning
confidence: 99%
“…Diagnosis codes, which are contained in administrative claims databases, are commonly used to identify children with chronic diseases such as asthma, diabetes, and inflammatory bowel disease . Several studies have demonstrated that administrative claims using ICD‐9‐CM diagnosis codes can be used to accurately identify children with sickle cell disease . However, these definitions are subject to two limitations in assessing health services among children with SCA: (a) identification of children with sickle cell disease more broadly as opposed to children with SCA; and (b) use of ICD‐9‐CM diagnosis codes.…”
Section: Introductionmentioning
confidence: 99%